Rumah Mutia : Implementasi Literasi Digital Di Era Revolusi Industri 4.0 Pada Suku Anak Dalam Di Desa Nyogan: Indonesia - Dermawan, Fito; Haerulloh Zikri, Muhammad; Naim, Ahmad Khoirul; Nur Izzaty, Chairunnisa; Wahyuni, Anny (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2022)
The writing of this community service article is the result of activities carried out to provide socialization and implementation of the application of digital literacy in the era of the industrial revolution 4.0 in the Suku Anak Dalam (SAD) in Nyogan Village. Community service activities for the Suku Anak Dalam (SAD) community in RT 15, Nyogan Village, Mestong District, Muaro Jambi Regency. This activity is carried out as an effort to introduce Digital Literacy skills and is expected to provide awareness that the Suku Anak Dalam community in Nyogan Village are able to contribute to the success of digital transformation and eliminate negative stigma among the general public. The method used by the Jambi University PKM-PM Team is community service with ice breaking to build the enthusiasm of the participants then provide socialization and assistance to achieve the goals of implementing community service. The results obtained from this activity are that the development of digital literacy will increase the potential of the Nyogan village community to continue to increase both from SDM and SDA.Keywords: industrial revolution, digital literacy, Suku Anak Dalam, nyogan village